#### Answer

y = 1
x = 2

#### Work Step by Step

x + y = 3 ; x = 2y
Substitute x for 2y to the first equation.
2y + y = 3
3y = 3 (Divide both sides by 3)
y = 1
Substitute y = 1 to the second equation
x = 2 $\times$ 1
x = 2

Published by
Pearson

ISBN 10:
0321726391

ISBN 13:
978-0-32172-639-1

y = 1
x = 2

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.